Observation of a crossover of S2n in the island of inversion from precision mass spectrometry - Kwiatkowski, Anna; Andreoiu, C.; Bale, J. C.; Chaudhuri, A.; Chowdhury, U.; Malbrunot-Ettenauer, S.; Gallant, Aaron; Grossheim, A.; Gwinner, G.; Lennarz, A.; Macdonald, T. D.; Rauch, T. J. M.; et al. (Physical review. C, Nuclear physics, 2015)
Mass measurements have been performed of the neutron-rich Al isotopes near N≈20, along the island of inversion. In general, the precision of the mass values was improved by an order of magnitude. Based on these new and more accurate data, we find the two-neutron separation energy of 3413Al to be 24.8(10.8) keV less than that of 3312Mg. This represents the first known crossover on the S2n surface of the chart of nuclides. Large-scale shell-model calculations show that the crossover can be attributed to exceptionally large energy gains of the Mg isotopes in the island of inversion.
Im Titel erscheint in der chemischen Formel das 2n tiefgestellt
Gesehen am 02.06.2020